Overcoming HCV treatment failure: From drug resistance to HCC: A case report - Kazakova, Evgeniya; Ibadullaeva, Nargiz; Ismoilov, Umed; Umurzakov, Bekzod; Musabaev, Erkin (Acta Biomedica Atenei Parmensis, 2025)
Chronic hepatitis C remains one of the leading causes of liver fibrosis progression, cirrhosis, and hepatocellular carcinoma. The introduction of direct-acting antiviral agents (DAAs) has significantly improved treatment outcomes, achieving a sustained virologic response (SVR) in most patients. However, in some cases, therapy fails due to the development of viral resistance, which is associated with mutations in therapy target regions of the viral genome. This article presents a clinical case of HCV drug resistance to DAAs, analyzes the possible reasons for treatment failure and detection of HCV-induced HCC, and discusses management strategies for such patients in the context of modern molecular diagnostics and personalized therapy approaches.